Giotto's remorse - Mallon, Darci (My University, 1982)
The mask worn by the female referenced a Japanese Noh theatre mask entitled, "The Blind Weakling." Although the artist was not the female in the painting, the image was essentially a self-portrait. Acrylic on four canvas covered panels, 11 feet x 7 feet. Collection of the Alberta Foundation for the Arts.
Exhibitions: 1984 The Summer Show, Robert Vanderleelee Gallery, Edmonton, Alberta 1982 Recent Works, Woltjen/Udell Gallery, Edmonton, Alberta
Keywords: Giotto; spatial illusions; Noh theatre; female nude in painting; acrylic painting